COMPARISONS OF SELF-EFFICACY AND HOPE AMONG STUDENTS WITH AND WITHOUT LEARNING DISABILITIES (Journal of Special Education and Rehabilitation, 2026)
Learning disability is a life-long condition that can affect academic functioning, everyday life and social life. In multiple areas, academic and other, students with LD often underachieve, and often with pervasive negative consequences. This study compared self-efficacy and hope in 30 elementary school (sixth grade) children with learning disabilities (LD) and 30 their peers without LD. An ex post facto design was used. Statistical population comprised of all students in elementary schools (sixth grade) in, Harsin, Iran, during the 2012-2013 academic year. Students with learning disabilities were randomly selected. The students with LD had been diagnosed by Colorado Learning Difficulties Questionnaire (CLDQ). The students completed the Wechsler Memory Scale, General Self-Efficacy Scale, and Children’s Hope Scale. Data were analyzed using analysis of variance. The Statistical Package for Social Sciences (SPSS 20) was used for computing descriptive statistics and analysis of variance. Differences were found between the groups on the self-efficacy and hope. The study demonstrated the important role of self-efficacy and hope for students with LD.
Keywords: Self-efficacy; hope; Learning Disabilities; Iran